Inside Front Cover: Anisotropic assembly and fluorescence enhancement of conjugated polymer nanostructures (View 6/2022). Issue 6 (19th December 2022) - Men, Xiaoju; Fang, Xiaofeng; Liu, Zhihe; Zhang, Zhe; Wu, Changfeng; Chen, Haobin
Abstract : Anisotropic assembly of conjugated polymers into complex nanostructures in a simple binary solvent.